A synthesized framework for the formation of startups' innovation ecosystem: A systematic literature review. Issue 5 (20th November 2019) - Ojaghi, Hamed; Mohammadi, Mahdi; Yazdani, Hamid Reza
Abstract : Purpose: The purpose of this study set out to introduce an alternative framework for explaining the formation of the innovation ecosystem based on the systematic literature review (SLR) and ecosystemic approach. Design/methodology/approach: This paper is an SLR of studies from the year 2008-2018 that investigating startups' innovation. SLR approach being used exploration, interpretation and communication method, which composed of seven steps as follows exploring topics, searching, organizing, evaluating and expanding, integrating and communicating. The output of this process is 63 documents that applied to synthesize the formation framework. Findings: The systematic review of literature has shown that researchers in recent years have considered some entities such as incubators, financials suppliers, accelerators, universities and companies in relation to the startup innovations, which are described in this paper as key actors. The study of the relationship between these actors in the documents led to the identification of interactional necessities, including structures, infrastructures and networks. Finally, the processes studied in the literature were classified into three types of mechanisms, namely, the genesis, growth and development of startups innovations. Research limitations/implications: The SLR approach is subject to limitations because some poor explanations amongst previous researchers may be repeated and reinforced. Also, in the protocol adopted in this paper, documents are limited in English. Practical implications: The introduced frammework can be useful in identifying and understanding the requirements of startups and creating effective policies for their innovation development. Originality/value: This paper reviews, summarizes and integrates the growing and scattered literature of the innovation ecosystem of the startups and delivers new facts for the future development of this field.